Thirty Years of Astronomical Discovery with UKIRT The Scientific Achievement of the United Kingdom InfraRed Telescope - Adamson, Andy.; Davies, John.; Robson, Ian.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
These are the proceedings of an international meeting hosted by the Royal Observatory, Edinburgh, to commemorate the 30th anniversary of the dedication of the UKIRT, the United Kingdom InfraRed Telescope. The volume comprises 31 professional level papers. The first part of the book has 10 thorough reviews of the conception, design and build of the telescope, as well as accounts of some its key instruments such as IRCAM (the common-user infrared camera), CGS4 (the fourth Cooled Grating Spectrometer) and the Wide Field Camera. The second part of the book comprises 14 reviews of scientific achievements during its twenty years of visitor mode operations. The final part of the book is a series of 7 reviews of the results from the multiple surveys being done as part of UKIDSS (UKIRT Infrared Deep Sky Survey). The authors are all experts in their respective fields, for example instrument scientists, operations staff and leading astronomers.
The UKIRT Success Story -- UKIRT - the Project and the Early Years -- The IRCAM Revolution -- Continuum Submillimetre Astronomy from UKIRT -- CGS4: A Breakthrough Instrument -- The UKIRT Upgrades Programme -- Operational Innovations -- The UKIRT Wide Field Camera -- Polarimetry at UKIRT -- UKIRT in the mid-Infrared -- Thirty Years of Star Formation at UKIRT -- Comets and Asteroids from UKIRT -- Spectroscopic Tomography of a Wind-collision Region -- Highlights of Infrared Spectroscopy of the Interstellar Medium at UKIRT -- UKIRT and the Brown Dwarfs: from Speculation to Classification -- White Dwarfs in UKIDSS -- Discovery of Variables in WFCAM and VISTA data -- Near Infrared Extinction at the Galactic Centre -- Observations of PAHs and nanodiamonds with UKIRT -- Nearby galaxies with UKIRT: uncovering star formation, structure and stellar masses -- WFCAM Surveys of Local Group Galaxies -- HiZELS: the High Redshift Emission Line Survey with UKIRT -- The HiZELS/UKIRT Large Survey for Bright Lya Emitters at z ~ 9 -- Observations of Gamma-Ray Bursts at UKIRT -- The UKIRT Infrared Deep Sky Survey (UKIDSS) : Origins and Highlights -- A Billion Stars: the Near-IR View of the Galaxy with the UKIDSS Galactic Plane Survey -- The UKIDSS Galactic Clusters Survey -- The UKIDSS Deep eXtralactic Survey -- UKIDSS UDS progress and science highlights -- Exploring Massive Galaxy Evolution with the UKIDSS Ultra-deep Survey -- The UKIRT Planet Finder.
Keywords: Physics; Observations, Astronomical; Astronomy -- Observations; Astrophysics; Cosmology; Physics; Astronomy, Observations and Techniques; Astrophysics and Astroparticles; Cosmology; Electronic books